Penerapan Model Pembelajaran STAD dalam Pembelajaran IPS untuk Meningkatkan Motivasi Belajar Siswa - Saidah Saidah (PAKIS (Publikasi Berkala Pendidikan Ilmu Sosial), 2022)
Improving learning motivation for students through effective learning models is important so that learning is more meaningful.  The purpose of this study is to describe the STAD learning model in social subjects to increase students' learning motivation. The research approach used was qualitative with the Class Action Research (CAR) method. The research subjects were students of class IX G SMPN 14 Banjarmasin in the 2019/2020 academic year. Research design started from planning, implementation, observation and reflection. To collect the data, this research used observation, assessment (test), discussion ( sharing ) and documentation. The results showed that the application of the STAD learning model was able to create a learning atmosphere that aroused excitement and enthusiasm for students’ learning, so that almost all students were motivated in social studies learning. This is indicated by the increasing number of students who are enthusiastic in the Social Sciences KBM process cycle II, which is 97% of all students in class IX G. The STAD learning model had succeeded in increasing students' learning motivation and is relevant to be applied in social studies subject. Keywords: Learning motivation, Student Teams-Achievement Divisions (STAD) learning model, Social Studies learning